Detection value of D-dimer, C-reactive protein, ESR and blood routine in the perioperative treatment of orthopaedic trauma patients: D-dimer, C-reactive protein and ESR in orthopaedic trauma - Kang Le; Li Chao; Pang Wei; Xue Shengkui; Ge Jun (Cellular and Molecular Biology, 2022)
The objective of this study was to analyze the detection value of D-dimer, C-reactive protein, ESR and blood routine in the perioperative treatment of orthopaedic trauma patients. For this aim, 86 orthopedic trauma patients who were treated at our hospital from December 2020 to December 2021 were selected as the study group, including 40 patients in the infected group and 46 patients in the uninfected group. 86 healthy people who were examined in our hospital were selected as the control group. D-dimer, C-reactive protein, ESR and blood routine test were given to the patients in the study group to evaluate the detection value of D-dimer, C-reactive protein, ESR and blood routine test in the perioperative treatment of orthopaedic trauma patients. Results indicated that compared with the control group, the levels of D-dimer, C-reactive protein, erythrocyte sedimentation rate, white blood cell and neutrophil in the study group were higher than those in the control group, With statistical difference (P < 0.05); Compared with the uninfected group, the levels of D-dimer, C-reactive protein, erythrocyte sedimentation rate, white blood cell and neutrophil in the infected group were higher than those in the uninfected group, With statistical difference (P < 0.05). Conclusion: Using D-dimer, C-reactive protein, ESR and blood routine to treat orthopaedic trauma patients in the perioperative period has good clinical detection value.